2023
DOI: 10.1002/adhm.202203104
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid‐Based Bioconjugate Systems, Scaffolds, and Their Therapeutic Potential

Abstract: In recent years, the development of hyaluronic acid or hyaluronan (HA) based scaffolds, medical devices, bioconjugate systems have expanded into a broad range of research and clinical applications. Research findings over the last two decades suggest that the abundance of HA in most mammalian tissues with distinctive biological roles and chemical simplicity for modifications have made it an attractive material with a rapidly growing global market. Besides its use as native forms, HA has received much interest o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 158 publications
0
12
0
Order By: Relevance
“…MeHA was chosen as the raw material for the microneedle part due to its excellent biocompatibility, which ensures the safety of the USMD. [ 11 ] Additionally, MeHA has supreme water absorbency, enabling the microneedle to rapidly absorb water and the drug molecules contained within it during the transitioning from a dry state to its maximum swelling state. [ 12 ] Unlike the previously reported hydrogel microneedle patch, where both the microneedles and base substrate were made of hydrogel materials, we utilized resin to create the base substrate of USMD.…”
Section: Resultsmentioning
confidence: 99%
“…MeHA was chosen as the raw material for the microneedle part due to its excellent biocompatibility, which ensures the safety of the USMD. [ 11 ] Additionally, MeHA has supreme water absorbency, enabling the microneedle to rapidly absorb water and the drug molecules contained within it during the transitioning from a dry state to its maximum swelling state. [ 12 ] Unlike the previously reported hydrogel microneedle patch, where both the microneedles and base substrate were made of hydrogel materials, we utilized resin to create the base substrate of USMD.…”
Section: Resultsmentioning
confidence: 99%
“…Although few studies have been reported on the neuroprotective function of FA, ,, to the best of our knowledge, its application in the lesion site, especially in the intermediate phase of SCI, has not been studied so far. The conjugates could provide synergistic and multitarget action . Different from previous studies in which FA was administered orally or systemically, which can be associated with side effects and poor bioavailability, in this work, we propose that covalent conjugation not only could improve the efficacy of FA as a neuroprotective agent but also could ameliorate the physicochemical properties and biological activity of the desired hydrogel compared to unconjugated HA-based hydrogel.…”
Section: Introductionmentioning
confidence: 91%
“…Targeting HA-mediated pathways, including HA synthesis, degradation, and interactions with specific receptors, holds promise for developing disease-modifying therapies [ 147 ]. Additionally, emerging techniques like tissue engineering and nanotechnology present exciting opportunities for HA-based interventions [ 148 ].…”
Section: Therapeutic Approachesmentioning
confidence: 99%